Introduction of Biotechnology in India's Agriculture Impact, Performance and Economics - Gandhi, Vasant P.; Jain, Dinesh (Springer Nature Singapore : Imprint: Springer, 2016)
Biotechnology can bring major breakthroughs in agriculture. The book examines the experience of introduction of biotechnology in Indian agriculture, specifically, examining the performance of Bt cotton versus non-Bt cotton across India's major cotton states, namely Andhra Pradesh, Gujarat, Maharashtra and Tamil Nadu, which together account for nearly 70 percent of the country's cotton production. Major advances in biotechnology have made it possible to directly identify genes, determine their functions, and transfer them from one organism to another. The advances have spawned many technologies and Bt cotton is one important outcome. Bt cotton has become one of the most widely cultivated transgenic crops and is currently grown in 21 countries - 11 developing and 10 industrialized countries. The Government of India was relatively late in permitting biotechnology, only approving the cultivation of three transgenic Bt cotton hybrids from April 2002. Many concerns were raised about their performance there was strong opposition from some quarters. In India, Gujarat and Maharastra were the first states to adopt them, followed by Andhra Pradesh, Karnataka, Tamil Nadu and Madhya Pradesh. Based on a sample of 694 farming households, the book examines and analyzes the performance on the yields, pesticide costs, seed costs, overall production costs and profits. It also reports on the environmental impacts, satisfaction with the technology and ways of improving its performance.